2022
DOI: 10.3390/su142416517
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Characteristics of Leaf, Litter and Soil during Vegetation Succession in Maolan National Nature Reserve, Guizhou, China

Abstract: Carbon (C), nitrogen (N), phosphorus (P) and potassium (K) are the main nutrient elements widely found in soil, litter and leaves, and their stoichiometric ratios are important indicators of ecosystem functions. However, there is little research on the effects that nutrient cycle and vegetation succession have on leaf, litter and soil nutrients and stoichiometric ratios, especially in the fragile karst areas. To reveal the nutrient cycling characteristics and ecosystem stability mechanism during vegetation suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
3
3
1
Order By: Relevance
“…Therefore, vegetation restoration could increase SOC and TN through multiple mechanisms such as litter and root turnover and biological N fixation in the study area. The findings from numerous studies are consistent with our results ( Xu et al., 2018 ; Su et al., 2019 ; Wu et al., 2022 ). It has been suggested that the vegetation biomass increment leads to an increase in P uptake by plants and therefore a decrease in soil P content ( Chen et al., 2000 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, vegetation restoration could increase SOC and TN through multiple mechanisms such as litter and root turnover and biological N fixation in the study area. The findings from numerous studies are consistent with our results ( Xu et al., 2018 ; Su et al., 2019 ; Wu et al., 2022 ). It has been suggested that the vegetation biomass increment leads to an increase in P uptake by plants and therefore a decrease in soil P content ( Chen et al., 2000 ).…”
Section: Discussionsupporting
confidence: 93%
“…The soil C:P ratio is an indicator of soil P effectiveness and a measure of soil P immobilization by soil microorganisms ( Tian et al., 2010 ), and soil N:P ratio is a predictor of N saturation and can be used to evaluate nutrient limitation thresholds ( Peñuelas et al., 2012 ). In the present study, soil C:P and N:P ratios increased significantly with vegetation restoration ( Table 2 , Figures 2E, F ), which is similar to the findings reported in many previous studies ( Xu et al., 2018 ; Lu et al., 2022 ; Wu et al., 2022 ). SOC and TN content increased with vegetation restoration, but TP content did not change significantly ( Figures 2A–C ), leading to the increase in soil C:P and N:P ratios, confirming that the potential of soil microorganisms to release P from mineralized organic matter gradually decreases or remains stable over the different restoration stages.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations